A community-based adapted exercise program to increase quality of life and self-efficacy among adults with physical disabilities: A mixed-method study. Issue 1 (8th February 2023) - Oh, Juntack; Davis, Ronald
Abstract : Background: Self-efficacy is one of the key constructs that directly influence physical activity, community participation, and mental health while acting as a strong influence on the quality of life (QOL) for adults with physical disabilities (AWPDs). There are relatively few studies focusing on a community-based exercise program in this population. Objective: This study aims to quantitatively examine a community-based adapted exercise program on the QOL and self-efficacy of AWPDs. In addition, we explored AWPD's perceived benefits of community-based exercise programming and any factors that may influence those perceived benefits. Method: Adults with physical disabilities (N = 50) participated in a 9-week community-based adapted exercise program (90-minute session, twice per week). QOL (WHOQOL-BREF) and self-efficacy were measured at baseline and at the conclusion of the program. A follow-up focus group (n = 22) was conducted at the postprogram. Quantitative data were analyzed by paired t test (α = 0.05). Qualitative data were analyzed by thematic coding and content analysis. Result: Significant improvement with moderate effect size was found across all variables. Two main themes emerged from the qualitative analysis: 1) perceived benefit of exercise program and 2) factors of an exercise program for AWPD. Conclusion: A community-based exercise program and self-efficacy play a large role in the exercise behaviors and QOL of AWPDs. The benefits of exercise and factors identified as promoting exercise may be carefully considered to improve QOL for this population. The finding of this study offers practical recommendations to community-based exercise specialists, which would assist in establishing an appropriate exercise program for AWPDs.